Feed Assessment Tool (FEAST) data repository website version 2.0.0 - Duncan, Alan J.; Fraval, Simon; Orth, Alan S.; Teufel, Nils (International Livestock Research Institute, 2021)
The Feed Assessment Tool (FEAST) is a systematic method to assess local feed resource availability and use. It helps in the design of intervention strategies aiming to optimize feed utilization and animal production.